The Types and Functions of Feedback in Dialogical Political Communications - Melkonyan, Nvard (Journal of Sociology: Bulletin of Yerevan University, 2017)
This article reviews the problem of providing one of the main components of the political dialogical communicative process: the construction of effective feedback. This article considers the essence of political communication at the present stage of development of the society, discusses definitions of the concept "feedback", presents functions and types of feedback in political communications, as well as analyzes prevalent communication barriers and conditions for providing effective political dialogue.